Impacts of Floods on Urban Settlements and the Adjacent Marine Environment: Evidence from Derna City - Saeed Hamed AL-Dahia; Amani Fitori Ali (المجلة الأفروآسيوية للبحث العلمي, 2025)
Floods are among the most lethal natural calamities, both for coastal urban areas and marine ecosystems. In September 2023, Derna city in Libya was hit by catastrophic flooding caused by Storm Daniel, registering immense human and material losses, as well as drastic environmental change to the adjacent marine ecosystem. This study discusses the impacts of flooding on marine environment and urban infrastructure in Derna City based on official reports, previous studies, satellite imagery, and post-disaster survey. It presents the degradation of infrastructure, increased coastal pollution, water quality fluctuation, and damage to marine habitats along the mouth of Wadi Derna. Recommendations are coastal disaster risk management plans and regular monitoring of flood impacts on the marine environment.